Systematic review of Halioticida noduliformans infection in South African abalone (Haliotis midae) - Thompson, P.N. (Peter N.) (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Epidemiology))--University of Pretoria, 2023.